The Influence of Perceived Benefits, Perceived Ease of Use, And Perceived Risk on MSME Decisions in Using QRIS as a Digital Payment System in Surakarta - Setyaningtyas, Riris Angga; Suranto, Suranto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this study is to ascertain how MSMEs engaged in batik artisan business in Surakarta decide whether to adopt QRIS (Quick Response Code Indonesian Standard) as a digital payment method, based on their perceptions of the advantages, convenience, and risk. The study used a correlational design with a quantitative approach. This study uses primary data that was gathered from 100 batik artisan MSME owners utilizing a four-point Likert scale questionnaire. SEM-PLS (Structural Equation Model-Partial Least Square) was used for data analysis. The findings show that MSME decisions to use QRIS are significantly influenced by perceived benefits and convenience. This shows that MSMEs feel the benefits, convenience, and benefits of using QRIS. Meanwhile, risk perception does not have a significant effect. This shows that the decision to use QRIS is not influenced by risk perception. Thus, the findings of this study offer an understanding of the elements that affect the adoption of QRIS and form the basis for further security and education improvements regarding the adoption of QRIS as a digital payment system among MSMEs.